2019
DOI: 10.21613/gorm.2018.789
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis and Fetal Outcomes of Cystic Hygroma: Experience of a Tertiary Hospital

Abstract: <p><strong>Objective:</strong> Cystic hygromas of nuchal origin are reported to be associated with fetal aneuploidy and structural anomalies in 50-80% of the cases. We aimed to report our experience on cystic hygromas via 18 cases.</p><p><strong>Study Design:</strong> We conducted a retrospective study based on a review of medical records of patients who had fetal septated cystic hygroma, diagnosed by ultrasonography, in the Ankara University School of Medicine, Depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
2
2
Order By: Relevance
“…In terms of pregnancy outcome, the rate of full-term delivery of a fetus with CH fluctuates between 7.5% and 18.8%. [13,15,32] In this study, the full-term delivery rate of fetuses with CH was 30.8%, which was higher than that reported in the literature. The prognosis of isolated CH with a normal genome is generally good under normal birth conditions.…”
Section: Discussioncontrasting
confidence: 66%
“…In terms of pregnancy outcome, the rate of full-term delivery of a fetus with CH fluctuates between 7.5% and 18.8%. [13,15,32] In this study, the full-term delivery rate of fetuses with CH was 30.8%, which was higher than that reported in the literature. The prognosis of isolated CH with a normal genome is generally good under normal birth conditions.…”
Section: Discussioncontrasting
confidence: 66%
“…In terms of pregnancy outcome, it has been reported that the rate of full-term delivery of fetus with CH uctuates from 7.5-18.8% [10,32,33]. In this paper, the full-term delivery rate of fetuses with CH was 30.8%, which was higher than that reported in literature.…”
Section: Discussioncontrasting
confidence: 54%
“…Generalized edema and hydrops may be the cause of left atrium dysfunction and aorta due to a compression effect leading to fetal death. In the literature, only a few studies have reported the resolution of hydrops and healthy newborns (11); the majority of the studies demonstrate that hydrops is associated with poor fetal outcomes (6,10,12,13). On the other hand, the resolution of nuchal edema with a normal karyotype is a good prognostic marker in the absence of any coexisting malformation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported poorer perinatal outcomes in pregnancies with fetal cystic hygroma and associated aneuploidy (5,6). We conducted this retrospective study to evaluate the pregnancy outcomes of fetuses with cystic hygroma either with normal karyotype or with no karyotype analysis in the prenatal period.…”
Section: Introductionmentioning
confidence: 99%